Endocapsular phacoemulsification without hydrodissection: an effective technique for cataract surgery following anterior capsular tear. Issue 8 (24th July 2008) - Angunawela, R I; Little, B
ABSTRACT: A radial tear of the anterior capsule can occur either as a primary tear-out during capsulorrhexis or as a secondary event during phaco. Endocapsular surgery in this situation is hazardous and the risk of posterior propagation of the tear is significantly increased by performing hydrodissection. We describe an alternative technique of endocapsular phacoemulsification without primary hydrodissection. The risk of tear propagation is reduced whilst at the same time auto-hydrodissection of the cortico-capsular connections occurs, enabling rotation and removal of the nucleus. This simple modification of conventional phacoemulsification reduces the risk of posterior extension in cases of radial anterior capsular tear and allows the relatively safe completion of endocapsular phacoemulsification. To view the full report and accompanying video please go to: http://bjo.bmj.com/cgi/content/full/92/8/1054/DC1 All videos from the BJO video report collection are available from: http://bjo.bmj.com/video/collection.dtl